(untitled) (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2026)
Coffee Shops in Indonesia are experiencing very rapid growth, making it one of the most dynamic and competitive Food & Beverage business sectors. This study was conducted on Kaldi Coffee Shop Pekanbaru customers with the aim of determining the effect of Storeosphere and Service Quality on Repurchase Decisions with Consumer Satisfaction as an intervening variable. The research sample consisted of 99 respondents of Kaldi Coffee Shop Pekanbaru customers selected using purposive sampling techniques with certain criteria. Data were obtained through questionnaires and then analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS software. The test results show that Store Atmosphere has a positive and significant effect on Consumer Satisfaction, and a significant effect on Repurchase Decisions. Service Quality is also proven to have a positive and significant effect on Consumer Satisfaction, and a significant effect on Repurchase Decisions. Consumer Satisfaction is proven to have a significant effect on Repurchase Decisions. Indirectly, Store Atmosphere has a significant effect on Repurchase Decisions through Consumer Satisfaction, and Service Quality has a significant effect on Repurchase Decisions through Consumer Satisfaction. This shows that customer experience supported by an aesthetic cafe atmosphere and excellent service is able to build consumer satisfaction, which then becomes the main driver of repeat purchase loyalty at Kaldi Coffee Shop Pekanbaru